The Right to Be Heard in the European Union – Case Law of the Court of Justice of the European Union - Beqiraj (Mihani), Pranvera (European Journal of Multidisciplinary Studies, 2016)
The right to be heard as a fundamental right within the Europen legal order was included in the right to good administration in the Charter of Fundamental Right of the European Union and imposes that every person has the right to be heard before any individual measure which would affect him or er adversely is taken. However, the Court of Justice of the European Union has a consolidated jurisprudence regarding the right to be heard which has already recognized it as a general principle and fundamental right. This paper will analyze this case law , which determine the nature of the decision-making process where this right must be applied, the nature of the decision taken and the way the interests of the person concened are affected. For this purpose different decisions of the Court of Justice of the European Union are taken under study.